Alat Pendeteksi Asap Rokok Dengan Peringatan Suara Di Kawasan Bebas Asap Rokok Di Lingkungan Polman Babel - Haniza, Haniza; Pamungkas, Berlian; Saputra, Zanu; Novitasari, Novitasari (Manutech : Jurnal Teknologi Manufaktur, 2025)
Polman Babel, which is one of the places for the nation's next generation to carry out the teaching and learning process in Bangka Regency, responds positively to regulations related to the No Smoking Area (KTR). This is realized by the presence of warning boards regarding the prohibition of smoking at several locations. The smoke-free area policy has been enforced, but there are still some violators and lack of awareness to comply with the regulation. To overcome this problem, a smoke detector is needed that can be used in the campus environment. A cigarette smoke detector using an MQ-135 sensor and an MQ-2 sensor that can emit a sound to encourage smokers to put out their cigarettes and leave the area was made. Detection tests were carried out with the distance of the sensor from the measured source of 1 meter to 3 meters and the calculation of the time from the appearance of smoke to the warning sound from the loudspeaker. The farther the sensor is from the smoke source, the smaller the detection value will be, depending on the position of the sensor and the smoke source. The sensor position that is accurate in detection is the sensor with the position facing down because it directly hits the smoke source. Like the nature of smoke that spreads from low places spreads towards the top.